2020
DOI: 10.2298/pan170531001s
|View full text |Cite
|
Sign up to set email alerts
|

Wagner versus Keynes: Empirical evidence from Turkey’s provinces

Abstract: Wagner's law and Keynes' hypothesis has long been debated in economics. In this paper, we test the income-expenditure hypothesis for eighty-one of Turkey's provinces for the period 1992 to 2013 using panel data analysis. For this purpose, the validity of these hypotheses is tested by applying recent panel cointegration and causality techniques, allowing for cross-sectional dependence and heterogeneity between regions. Under the presence of cross-sectional dependence and heterogeneity, the level of integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…As a result, the specification and estimation of the linear PMG model are reliable and precise. Hazarika and Nayak (2022), Sagdic, Sasmaz, and Tuncer (2020) and Narayan et al (2012), which supported the notion of a bidirectional relationship between public expenditure and economic growth, aligning with both Wagner's law and Keynes' hypothesis. However, the conclusions drawn from the research Rani and Kumar (2022) are consistent with the present study's findings, suggesting that for the Indian states examined, Wagner's law holds true while Keynesian hypothesis is rejected.…”
Section: Resultssupporting
confidence: 55%
“…As a result, the specification and estimation of the linear PMG model are reliable and precise. Hazarika and Nayak (2022), Sagdic, Sasmaz, and Tuncer (2020) and Narayan et al (2012), which supported the notion of a bidirectional relationship between public expenditure and economic growth, aligning with both Wagner's law and Keynes' hypothesis. However, the conclusions drawn from the research Rani and Kumar (2022) are consistent with the present study's findings, suggesting that for the Indian states examined, Wagner's law holds true while Keynesian hypothesis is rejected.…”
Section: Resultssupporting
confidence: 55%
“…Using Johansen's cointegration test and Granger's causality test for the period 1975-2014, Uzuner et al [53] confirm Wagner's law through the existence of a long-term relationship between public expenditures and economic growth in Turkey. Moreover, Sagdic et al [54] provide strong support not only for Wagner's law but also for Keynes' hypothesis in the case of the 81 provinces of Turkey. Focusing on health expenditure, Atilgan et al [55] concluded that there is a dynamic causal relationship between them and economic growth in Turkey.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Paparas et al [50] estimated a value of 1.19 for the long-run equilibrium elasticity in the UK (1850-2010). Using annual panel data for 81 provinces in Turkey (1992-2013), Sagdic et al [51] estimated a value of 0.58 for the long-run equilibrium elasticity. Peña [4] estimated the long-run equilibrium elasticity equal to 0.10 in Venezuela .…”
Section: Gupta and Michasmentioning
confidence: 99%
“…Considering the measures of government size and economic growth, according to Granger causality results with time series data or panel data, Magazzino [28], Barra et al [36], Irandoust [37], and Nyasha and Odhiambo [30] indicated the existence of four possible hypotheses: Wagner's law, in which unidirectional causality runs from economic growth to public expenditure [3,25,[38][39][40][41][42][43][44]; the Keynesian hypothesis, in which unidirectional causality runs from public expenditure to economic growth [4,45]; feedback hypothesis, in which a bidirectional causality flow exists between economic growth and public expenditure [33,[46][47][48][49][50][51]; and neutrality hypothesis, verified with variables that do not exhibit Granger causality in both directions [3,17,52].…”
Section: Introductionmentioning
confidence: 99%